Exploring lower secondary school teachers' perceptions of integrating simulations into chemistry instruction - Jane Batamuliza; Gonzague Habinshuti; Jean Baptiste Nkurunziza (Frontiers in Education)
IntroductionTeachers play a crucial role in guiding students to enhance their learning and achieve academic goals. Understanding their perspectives on educational technology is essential to fostering effective integration into classroom instruction. This study investigates the perceptions of lower secondary school chemistry teachers regarding the ease of use and usefulness of integrating ICBLS into teaching.MethodsA multiple case study design was employed, involving eight chemistry teachers from four schools where ICBLS had been implemented. Data were collected through semi-structured interviews, group discussions, professional workshops, and classroom observation. The data were transcribed and analyzed thematically using NVivo 14 software.ResultsThe findings indicate that teachers hold positive perceptions of ICBLS, citing benefits such as enhanced safety, collaboration learning, and hands-on activities. However, challenges were identified, including limited access to computers and insufficient professional training.DiscussionThe study underscores the importance of addressing technical and training barriers to optimize the use of ICBLS. Recommendations include strengthening professional development, fostering peer collaboration, aligning curricula with ICBLS, and ensuring administrative support and provision of adequate resources.